Studi Penambatan Molekul Flavonoid Pada Reseptor α-Glukosidase menggunakan PLANTS - Budi Mulyati; Riong Seulina Panjaitan (JURNAL KIMIA MULAWARMAN, 2021)
ABSTRACT Plants that contain flavonoids are widely used in traditional medicine. Flavonoids can reduce blood glucose levels with their ability as anti-oxidants. The purpose of this study was to determine natural compounds from flavonoid derivatives that have good affinity and conformation and their interactions in inhibiting α-glucosidase (an enzyme that breaks down carbohydrates into glucose) and determine the sequence of ligands that interact more strongly with α protein / enzyme α-glucosidase. Molecular docking is a computational method that aims to imitate the interaction of a ligand molecule with the protein it targets in in-vitro tests. Molecular docking between flavonoids and α-glucosidase receptors was carried out using the PLANTS method to see its affinity. The flavonoids used as ligands were flavones, flavanols and chalcone with the results of the docking scores respectively, -65.41, -64.39 and -63.07 where the standard ligand used in this study was deoxynojirimycin (-77.12). In the active side of the α-Glucosidase enzyme that binds to flavonoid ligands is Gly 555, Glu 526 and Pro 556.